Transtorno bipolar do humor e gênero - Dias, Rogerio [UNESP]; Kerr-Corrêa, Florence [UNESP]; Torresan, Ricardo Cezar [UNESP]; Dos Santos, Carlos Henrique R. (FapUNIFESP (SciELO), 2006)
Although the bipolar disorder (BD) occurs almost with the same frequency in both genders, the phenomenology and the outcome of the illness differ between them. Nevertheless, there is evidence that women with BD show, more than men, delayed beginning, especially in their fifth decade, more rapid cycling outcome, more depressive episodes, more dysphoric mania, more mixed states and more BD type II. Even so, the findings are not always consistent. Although the risk of comorbidities in BD includes, for both the sorts, excessive alcoholic consumption and drugs, bipolar men would have greater probability of being alcohol dependent, of not seeking treatment and of committing suicide. Suggested hypotheses to explain such differences vary from those centered in cultural or psychological aspects to those that focus on the steroids hormones, and other hormones such as cortisol, thyroid hormones and even on the cerebral anatomy. The reproductive cycle (menstrual cycle, pregnancy and menopause) influences on the BD phenomenology and its relevance to the therapeutical options in the treatment of the BD in women are presented in the last part of this review. Further investigations must to be done in order to clarify this controversy. However, up to now the data indicate that estrogen therapy is not to be primarily indicated to prevent depression, Alzheimer disease or cognition impairment.
Bipolar affective disorder and gender
Keywords: Bipolar disorder; Epidemiology; Gender; Outcome; Treatment; alcoholism; bipolar disorder; bipolar II disorder; bipolar mania; comorbidity; depression; drug dependence; human; phenomenology; review; risk assessment; sex difference; suicide attempt